France in revolution 1774-1815 - Rees, Dylan (Access to history, 2019)
Exam board: AQA; Pearson Edexcel; OCR Level: AS/A-level Subject: History First teaching: September 2015 First exams: Summer 2016 (AS); Summer 2017 (A-level) Put your trust in the textbook series that has given thousands of A-level History students deeper knowledge and better grades for over 30 years. Updated to meet the demands of today's A-level specifications, this new generation of Access to History titles includes accurate exam guidance based on examiners' reports, free online activity worksheets and contextual information that underpins students' understanding of the period. - Develop strong historical knowledge: in-depth analysis of each topic is both authoritative and accessible - Build historical skills and understanding: downloadable activity worksheets can be used independently by students or edited by teachers for classwork and homework - Learn, remember and connect important events and people: an introduction to the period, summary diagrams, timelines and links to additional online resources support lessons, revision and coursework - Achieve exam success: practical advice matched to the requirements of your A-level specification incorporates the lessons learnt from previous exams - Engage with sources, interpretations and the latest historical research: students will evaluate a rich collection of visual and written materials, plus key debates that examine the views of different historians.